Reforma tributária e reflexo nas finanças públicas estaduais: o caso do Estado de Sergipe - Santos, Sérgio Luiz Silva (2013)
The objective of this dissertation is to measure the impact of a tax reform may cause the finances of federal units and in particular how it will affect the state of Sergipe. This work also aims to evidence the importance of tax reform to the development and demonstrate many aspects inherent to its discussion that has been occupying a prominent place in the national policy agenda, from the simplest citizen by those who are part of the senior government. Also seeks to address the reform of our fiscal federalism in view of the question of the distribution of tax revenues present tensions in the political and economic relations between the entities that have the power to impose and collect taxes that support the process of tax competition, even with the breakdown of constitutional rules and parallel feeds serious problem of regional inequalities. An important lesson that history provides for the necessary changes to the recovery of the qualities of the GST is that they should be addressed within the framework of a reform that aims at the reconstruction of the Brazilian fiscal federalism in order to restore balance and promote cohesion federal. This work intends to contribute to the debate on the reform needed to correct the distortions accumulated ICMS since birth, feeding federal conflicts, generate economic inefficiency, and create social inequities entail significant challenges for the future of the federation, in other words, there is a need to design a new tributary system which in many aspects is affected by the coalition of political forces in that federated units (Union, states, municipalities and the Federal District) or part of them detect imbalance or disproportion between the revenue received and their responsibilities.